Kombinasi Tepung Bunga Marigold (Tegates arecta) dan Tepung Labu Kuning (Cucurbita moschata Duch) Terhadap Tingkat Kecerahan Warna Ikan Komet (Carassius auratus) - Kristiana, Ela; Salosso, Yuliana; Djonu, Asriati (Jurnal Aquatik, 2024)
Fish color may be enhanced by caratenoids found in yellow pumpkin (Cucurbita moschata Duch) and marigold flower flour (Tegates arecta). The aim of this study was to determine the effect of feeding comet fish (Tagetes sp.) a mixture of marigold flour (T. arecta) and yellow pumpkin (C. moschata Duch) on the amount of brightness in their color. This study used the completely randomized design (CRD) method, with a design consisting of three replications and four treatments. According to the study's findings, treatment C, which included 80 g of marigold flower flour and 20 g of pumpkin flour per kilogram of feed, produced the best results. With a 63% survival rate, Treatment C produced an absolute weight gain of 4.3 g and a brightness value of 4.00. Keywords: Marigold flowers, Carassius auratus, color quality, yellow pumpkin